pelatihan calon para legal pelatihan/pendidikan calon para legal di GKJTU Klasis Getasan dan Klasis Kopeng Kab. Semarang - Dwiyatmi, Sri Harini; Prasetyo, Abigail; Alfret, Alfret; Darmawan, Eric Sanjaya; Anindita, Hana Dwi; Putri, Devina Athalia; Le'bok, Lala Tiara; Burhanudin, Krisna; Nazara, Imanuel (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Church’s figures from GKJTU encountered with various legal problems and felt that they didn’t have any knowledge about law. Therefore, an incidental counselling was held to fulfil their desire in purpose to understand legal knowledge so that these figures might resolve legal problems in their environment. The church’s figures give the basic legal knowledge and anti-corruption education through the legal professionals’ trainer. This paralegal training is to equipped participants with better basic-practical legal knowledge to manage the legal problems they faced. By the end of the training, these participants will become the front guard to resolve the legal matters in their environment, as they will be called: paralegals